Manuel de droit civil et commercial anglais - Curti, Arthur
Bibliothèque technique [1]. Droit civil. - 1928. (8 décembre.) 316 p. 36 fr. [2361] ; II. Droit commercial. - 1929. (16 mars.) In-4, 463 p., 45 fr. [5234]